Level-8 Ph.D. Programs In Medical Sciences: High Time For The Higher Education Commission (HEC) Of Pakistan To Establish A Medical Wing - Omer, Wafa (Journal of Rawalpindi Medical College, 2024)
Medical Universities in Pakistan are growing in number at a fast pace. According to the database of the Pakistan Medical Commission 2021, at present Pakistan is home to 224 million people, 30 medical universities, and 176 public and private sector medical and dental schools.1 Most of these medical colleges have now transformed into autonomous medical universities while some remain affiliated with renowned medical universities.2 Some of the relatively newer medical universities in Punjab are Rawalpindi Medical University, Fatima Jinnah Medical University, King Edward Medical University, Nishtar Medical University and National University of Medical Sciences. The medical universities in Pakistan have started launching PhD programs in Basic and Diagnostic Medical Sciences and the trend towards opting for these prestigious programs is on the rise amongst the young physicians.3 The subjects being offered for pursuing PhD in the medical sciences by most of the medical universities across Pakistan are Anatomy, Physiology, Biochemistry, Pharmacology, Chemical Pathology, Haematology, Microbiology, Histopathology and Community Medicine. These degrees are full-time on-campus programs and face-to-face learning during the course is essential. The PhD trainees enrolled across all fields of Pathology are deputed in the diagnostic medical laboratories of the affiliated hospitals and are involved in clinical diagnostic work along with research. Doctors pursuing PhD degrees in other disciplines of Medicine are also given clinical exposure in the affiliated hospitals as they are already licensed medical practitioners and most of their research work is based on clinical scenarios.4 Since PhD in Basic and Diagnostic Medical Sciences has recently gained popularity amongst doctors who were previously primarily opting for fellowships and diplomas, therefore the program is still in its juvenile stages and the PhD policies and regulations are in the process of being compiled. The National Academy of Higher Education (NAHE) is organising master trainer programs for PhD supervisors across Pakistan but the representation of supervisors with both MBBS and PhD in these cohorts is scarce. The competency framework that is being developed for the PhD trainees across Pakistan is not tailored according to the needs of the practising physicians opting for a PhD in Medical Sciences across Pakistan.5 PhD in Urdu language, Agriculture Poultry science, biological sciences or other non-medical fields cannot have the same competency framework as that for medical professionals who are involved in diagnostic and clinical work in the hospitals along with research dealing with human subjects and patients. A physician cannot be asked to opt out of clinical setups and hospitals upon completion of a PhD degree labelling it as an academic or research degree because the doctors who are opting for this level-8 degree are primarily physicians and they cannot be detached from the clinical environment. However, developing a proper competency framework with the inclusion of clinical modules uniformly across all these fields can improve the quality and ensure standardisation across all disciplines in Medical and Diagnostic Sciences. A medical doctor cannot be an Academician, researcher, or clinician individually as the practising physician has to work across all these domains at the same time during his tenure in a medical setup.6 The PhD programs in Basic and Diagnostic Medical Sciences in Medical Universities are governed by regulations formulated by both HEC and PMDC and not HEC alone. PhD according to HEC is classified as a Level-8 qualification7 and according to PM&DC, it is categorised as a Level-III qualification.8 There is a clear document given by HEC stating the requirements to be fulfilled by a Degree Awarding Institute to be given an NOC for starting a PhD program. This document is generalised and not specific to Medical Universities. PM&DC on the other hand has also laid down a clear charter for obtaining recognition of any PG program which is to be started in a Medical University which is exclusively formulated for Medical Degree awarding Institutes. HEC has recently emphasized repeatedly that a PhD program launched in a Medical University must be accredited by the governing council in this case being the Pakistan Medical and Dental Council. Challenges: The problem which is now being faced by the physicians opting for PhD in Basic and Diagnostic Medical Sciences is the lack of availability of standardised regulations which are acceptable to both HEC and PMDC. PMDC requires that the supervisor of a PhD in medical sciences should possess an MBBS degree along with a PhD in the respective subject. This is because the clinical correlation that is required for teaching these subjects to medical practitioners is only possible if the supervisor possesses an MBBS degree along with a PhD in the respective subject. The co-supervisor however may be non-medical as per need of the PhD research project. HEC has not laid down any guidelines in this regard and the supervisorship criteria remain generalised across all disciplines whether medical or non-medical. Moreover, as per PMDC policy, only a PhD degree in medical sciences from a Medical University will be recognised and endorsed on the medical practitioner’s license and that from a non-medical university will not be given due recognition, HEC on the other hand recognises both. It is of utmost importance that the PhD degree obtained by physicians in Medical Sciences must be recognised by both HEC and PMDC for them to practice in their respective fields and to apply for jobs abroad. PhD in medical sciences is relatively a newer domain as the trainee practices both as a physician and a researcher and requires expertise accordingly, therefore the curriculum and the competency framework for this degree require special attention by the regulatory bodies. Recently, a law which was passed by the regulatory body stated that a PhD degree is valid only in Basic and Diagnostic Medical Sciences and not in Clinical Sciences.9 Also, it stated that PhD degree holders should hold academic and research posts while doctors having fellowships and diplomas should be considered eligible for Clinical and Academic posts. How can a clinician not be a researcher considering the pace at which the global medical community and advancements in medical science are progressing and how can a practising physician bid farewell to clinical practice just because he is labelled to be a researcher only? Last but not least another major problem that is being faced by the post-graduate trainees during their studies is that the list of approved journals on the website of HEC differs from those which are approved or recognised by PMDC leading to further mayhem as the trainees remain in a state of uncertainty when it comes to publishing their research work.10,11 Recommendations: What is the way forward? It’s simple! The dire need of the hour is to encourage doctors to opt for specialization may it be PhD, Fellowship or MD/MS and the curriculum should be modified in a way to produce a multifaceted doctor who is an Academician, Researcher and clinician without restricting or creating undue hinderances in the progression of the medical community. Knowledge and skill in any form if planned according to a proper framework will always be beneficial for the community at large and in a country like Pakistan where we have a dire shortage of resources and manpower we should aim towards producing multifaceted doctors rather than restricting their field of expertise and limiting the available options for them to excel in their respective Medical Sciences fields. It is high time for HEC to establish a medical wing that is run by medical doctors possessing PhD in Medical Sciences so that they can work in close liaison with PMDC and develop standardised policies, guidelines and competency framework and save the doctors from undue stress after obtaining the PhD degree in medical sciences. PhD is one of the highest and most prestigious degrees in the country and even though a student’s primary aim must be to gain knowledge in his field at the same time it should be in line with the guidelines of the regulatory authorities and all regulatory authorities should devise uniform guidelines so that the student does not have to face any problem while applying for a job or being promoted. A student can excel and advance his knowledge only once the physiological needs are fulfilled according to Maslow’s theory; so the need to have a stable job and earn respectably cannot be ignored saying that knowledge alone is sufficient. Conclusion: Summing up the discussion I would conclude by stating that some of the important reasons for establishing a Medical wing in the Higher Education Commission of Pakistan are: To develop a comprehensive competency framework tailored according to the needs of the healthcare institutions and the expertise of the medical physicians opting for level-8 degrees. To build up a strong liaison and collaboration between HEC and PM&DC for devising uniform policies across all disciplines of Medical Sciences. To assess the demand for healthcare professionals doctors, nurses, and other healthcare workers in Pakistan. Evaluate the accessibility of medical education in the country. If there are limited medical schools or if access is restricted then creating a medical wing within higher education institutions can help address this issue. To align the policies with the national health priorities and goals set by the government to focus on which area of healthcare the healthcare professionals need to be trained more. To improve and create opportunities for collaboration between existing healthcare institutions to enhance the practical training and clinical exposure for post-graduate medical students. To analyze the market demand for specialized medical programs. If there is a demand for niche areas of healthcare, such as public health, medical research, or specialized medical fields, a medical wing could cater to these needs.